Cancer Risks Associated with External Radiation From Diagnostic Imaging Procedures - Linet, Martha S. (2012)
The 600% increase in medical radiation exposure to the US population since 1980 has provided immense benefit, but potential future cancer risks to patients. Most of the increase is from diagnostic radiologic procedures. The objectives of this review are to summarize epidemiologic data on cancer risks associated with diagnostic procedures, describe how exposures from recent diagnostic procedures relate to radiation levels linked with cancer occurrence, and propose a framework of strategies to reduce radiation from diagnostic imaging in patients. We briefly review radiation dose definitions, mechanisms of radiation carcinogenesis, key epidemiologic studies of medical and other radiation sources and cancer risks, and dose trends from diagnostic procedures. We describe cancer risks from experimental studies, future projected risks from current imaging procedures, and the potential for higher risks in genetically susceptible populations. To reduce future projected cancers from diagnostic procedures, we advocate widespread use of evidence-based appropriateness criteria for decisions about imaging procedures, oversight of equipment to deliver reliably the minimum radiation required to attain clinical objectives, development of electronic lifetime records of imaging procedures for patients and their physicians, and commitment by medical training programs, professional societies, and radiation protection organizations to educate all stakeholders in reducing radiation from diagnostic procedures.